Pendampingan Kader Posyandu Dalam Upaya Tracking Anak Zero Dose dan Missed Dose Imunisasi - Hamdin Hamdin; Abdul Hamid (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Immunization is a strategic and cost-effective effort to reduce the morbidity and mortality of children in the world. Immunization saves around 2 to 3 million lives each year. During the COVID-19 pandemic, immunization coverage has declined dramatically. The number of children with incomplete immunization status has increased. This community service is expected to increase the knowledge of posyandu cadres about Tracking Children with Zero Dose and Missed Dose Immunization. The training provided by implementing modules and animated videos prepared by the Ministry of Health is effective in increasing the knowledge of posyandu cadres in the Alas Health Center Work Area, Sumbawa Regency. This shows that modules and videos are good media in conveying information to training participants. Increased knowledge of posyandu cadres after receiving the training materials provided, Knowledge of health cadres increased, a significant increase before training only 10% of posyandu cadres had high knowledge of immunization, while after training it increased to 90%.